Strong short-term non-linearity of solar irradiance fluctuations. (1st March 2017) - Madanchi, Ata; Absalan, M.; Lohmann, G.; Anvari, M.; Reza Rahimi Tabar, M.
Highlights: The short-term non-linearity of solar irradiance fluctuations has been studied. We show that time series of solar irradiance have a long range correlation function. The fluctuations have multifractal behaviour. Abstract: We investigate short-term non-linearity of solar irradiance fluctuations using the multifractal detrended fluctuation analysis (MFDFA). The MFDFA shows that time series of solar irradiance have a long range correlation function with a multifractal behavior. We apply this method to solar irradiance time series from several regions around the world with resolutions of seconds and minutes. The obtained generalized Hurst and Renyi exponents h ( q ) and τ ( q ) suggest the non-linear and non-stationary essence of measured irradiance time series. Also, we analyze shuffled, random phase, and rank-wised surrogated data to reveal the nature of the multifractality and conclude that linear and non-linear correlations are the dominant contributions to observed multifractal and non-linear behavior of solar irradiance.